PENINGKATAN KEMAMPUAN PEMBELAJARAN KONSEP BANGUN DATAR SEGITIGA BERBANTUAN AUDIO VISUAL KELAS IV SD NEGERI 2 KEPIL KABUPATEN WONOSOBO - Fuad Al Haris; Yuli Widiyono; Arum Ratnaningsih (STKIP Subang, 2024)
This study aims to determine the improvement in learning interest and mathematics achievement in the topic of plane geometry, specifically triangles, with the assistance of audiovisual media in Grade IV of SD Negeri 2 Kepil. This research employed a Classroom Action Research design consisting of two cycles, with each cycle including two meetings. The subjects of this study were the fourth-grade students of SDN 2 Kepil, Wonosobo Regency, consisting of 5 males and 18 females. Data collection techniques included interviews and observations. The data analysis techniques used were both quantitative and qualitative analysis. Based on the results of the data analysis, it can be concluded that students' learning interest increased with the use of audiovisual media, with the average learning interest rising from 60% in the pre-cycle to 81% in the first cycle and 92.25% in the second cycle. Thus, the implementation of audiovisual media was effective in enhancing students' learning interest. Additionally, the students' academic performance improved with the use of audiovisual media, with the average score increasing from 59.3 in the pre-cycle to 69.8 in the first cycle and 80.2 in the second cycle. Therefore, the use of audiovisual media can significantly enhance students' academic achievement in the topic of plane geometry, specifically triangles.